Approaching Personality through Style: The Seriously Perplexing Figure of Dezső Szabó. (November 2013) - Abondolo, Daniel
<x content-type="archive" xml:space="preserve">Abstract</x> Dezső Szabó (born 1879, Klausenburg/Kolozsvár/Cluj, Austria-Hungary, died 1945, Budapest) was a towering figure of his generation. Literary critic, social pamphleteer, satirist, and novelist, he aroused strong passions on all sides with his rhetorically freighted prose and his fluid, yet forceful, political views. All accounts of his work concentrate on its intent, content, or consequences, and it is widely agreed that Szabó's 'style' was his most prominent trait. And yet it is as if the political and ideological impact of the man has all but eclipsed the writing itself: with the exception of one brief monograph of 1937, we have no study devoted to the detailed examination of the ways in which he used Hungarian. Such a study is what is attempted in this essay. The method is primarily linguistic: all pertinent features of Szabó's use of Hungarian are discussed, from the submorphemic (alliteration and other sound-patterning) through his immoderate derivational morphology, overstuffed noun phrases, and idiosyncratic lexis.